Out of control? Measuring a decade of EU regulation (London, 2009)
"Open Europe has published one of the most comprehensive studies ever undertaken of the cost of regulation introduced in the past decade in the UK. Analysing more than 2,000 Impact Assessments, Open Europe has found that regulations introduced between 1998 and 2008 have cost the UK economy